Investigation into how facilities management has evolved to support the hybrid and remote workplace trends - Jones, Shane (Department of Construction Economics and Management, 2025)
The purpose of this dissertation was to investigate how the facilities management profession in South Africa has been supporting the hybrid and remote work models. Furthermore, the study explored the management of hybrid and remote operationally and strategically, with an in-depth look into the equipment, logistics, skill sets and capabilities needed to successfully manage the hybrid and remote workplace models. The study considered the impact of the South African socio and economic landscape as one of the primary determinants towards the successful implementation and management of a hybrid and remote strategy, presently, and a future prediction based on the data presented. The primary motivation for the study was to adopt research within South Africa, as the data and information available reflected developed regions such as North America and Europe. The study revealed that the barriers and challenges faced in South Africa as a developing country and economy, would reflect the same barriers and challenges faced in developing and underdeveloped countries and economies around the world. There cannot be a copy and paste strategy for hybrid and remote, and the data, trends, and previous research available has very little representation for developing and underdeveloped countries and regions. The outcome of the study revealed that hybrid and remote models are limited due to the various challenges and barriers faced in South Africa, such as the lack of infrastructure, power supply instability, and poor internet supply as some of the primary challenges faced in the poorer communities, which creates an imbalance in the competitiveness of labour and talent. Additional skill sets and close collaboration with functional divisions such as IT and HR is critically important when implementing and managing hybrid and remote. The study also revealed that a well thought out and planned remote and hybrid strategy is necessary to address various organisational concerns such as maintaining the company culture, social connection, and collaboration, while promoting employee wellness. The study further revealed that REITs and property owners had repurposed buildings to attract back tenants that are in search of an enhanced workplace experience. Workplace experience, as a theme emerged as a central theme throughout the study. The research concluded that the hybrid and remote practices is in its infancy stage, and further research would be needed to better understand these practices within South Africa and the rest of the world.